Experimental observation of parametric X-ray radiation directed along the propagation velocity of relativistic electrons in a tungsten crystal; JETP Letters; Vol. 80, Iss. 6 - Baldin A. N.; Bogomazova E. A.; Vnukov I. E.; Kalinin B. N.; Kubankin A. S. Aleksandr Sergeevich; Nasonov N. N.; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Sharafutdinov A. F.; Aleinik A. N. Aleksandr Nikonorovich (2004, 2004)
Title screen